PENDIDIKAN KRISTEN DAN AMANAT AGUNG - Edu Arto Silalahi (Jurnal Arrabona, 2018)
Education is an ongoing process, from the past, now and in the future. Christian education in its nature is to guide one to exit the darkness in order live in accordance with God’s will. God’s will has been opened to the world thru revelation. Jesus Christ is the peak of the revelation. All christian education should, therefore, be centralized or based on Christ and His commission. His commission is plain: that all nations become His true disciples.